Equality or Reverse Suppression? Rethinking Affirmative Action For Women In African Politics - Chukwudi, Agunyai Samuel; AFOLABI, Israel Toba; Hofisi, Costa (Journal of Ecohumanism, 2025)
This paper examines the extent to which affirmative action for women in African politics has undermined democracy in selected African countries. It questions the possibility of affirmative action in the promotion of equality and fairness in democratic societies. This suspicion or question is based on the fact that, in an attempt to give affirmative action for women in African politics, critical democratic principles such as free, fair, and credible elections are sacrificed. This has had severe implications for good governance and democratic consolidation in most African countries, especially Nigeria. Drawing on qualitative data that was sourced through desktop reviews and analysis, this article examines how affirmative action for women in African politics is undermining the sacred democratic ethos in Africa. It argues that while affirmative action is meant to solve the problem of discrimination against women in African politics, it also highlights more ravaging problems limiting democratic consolidation in selected African states. It concludes that affirmative action within the confines of law, justice, and democratic principles is likely to deepen democracy in selected African states.